2019
DOI: 10.1186/s41180-019-0027-5
|View full text |Cite
|
Sign up to set email alerts
|

An emerging economy perspective on corporate sustainability reporting – main actors’ views on the current state of affairs in Pakistan

Abstract: The purpose of this paper is to explore the main actors' views on the current state of sustainability reporting in a developing country context. This qualitative study is based on the interviews of 20 individuals and organizations from Pakistan who were identified as main actors involved in the practice of sustainability reporting. This paper draws on the arguments of multiple theoretical frameworks, including legitimacy theory, stakeholders' theory, institutional theory, political cost theory, and signalling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 77 publications
(137 reference statements)
1
70
0
4
Order By: Relevance
“…This is exploratory qualitative research, designed to uncover trends in thought and opinions, and identify the problem currently being faced by different Humanitarian organizations during disaster relief (Wyse 2011). Moreover, Mahmood et al (2019) Also suggest that qualitative methods help to capture not only the stakeholders' perception but also elaborate on the context in which they are held. Therefore, to answer the research questions drafted for this study, we used the data triangulation approach.…”
Section: Methodsmentioning
confidence: 99%
“…This is exploratory qualitative research, designed to uncover trends in thought and opinions, and identify the problem currently being faced by different Humanitarian organizations during disaster relief (Wyse 2011). Moreover, Mahmood et al (2019) Also suggest that qualitative methods help to capture not only the stakeholders' perception but also elaborate on the context in which they are held. Therefore, to answer the research questions drafted for this study, we used the data triangulation approach.…”
Section: Methodsmentioning
confidence: 99%
“…The study indicated a positive impact of sustainable financial reporting on firm financial performance and concluded that enhanced financial performance of banks in Pakistan is connected with increase in sustainable financial reporting. A qualitative study was carried out by Mahmood et al (2019) to identify actors involved in sustainable financial reporting in Pakistan. Results suggested that local and international regulatory agencies, standards, foreign buyers, and sustainable reporting awards are important actors in the development and emergence of sustainable financial reporting in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We believe that these inherent tensions between long-established traditional institutions and the emergence of modern institutions have both direct and indirect impacts on the institutional logics and practices of sustainability reporting, which require exploration. In addition, the study on sustainability reporting in a context where very few companies comply even with mandatory disclosure requirements is indeed illuminating (Mahmood et al, 2017;Mahmood et al, 2019) The paper is structured as follows. Section 2 presents a review of the literature, focusing mainly on the competing nature of the sustainability construct and its reporting, as well as the diversity of practices and motivations.…”
Section: Introductionmentioning
confidence: 99%